2008
DOI: 10.1038/nrc2507
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and their relationship to the symptoms and outcome of cancer

Abstract: Tumours contain immune cells and a network of pro- and anti-inflammatory cytokines, which collaborate in the development and progression of cancer. Cytokine profiles might prove to be prognostic. The systemic effects of pro-inflammatory cytokines are associated with fatigue, depression and cognitive impairment, and can affect quality of life before, during and after treatment. In people with advanced cancer, pro-inflammatory cytokines are additionally associated with anorexia and cachexia, pain, toxicity of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
487
1
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 569 publications
(528 citation statements)
references
References 246 publications
(224 reference statements)
14
487
1
26
Order By: Relevance
“…Recent studies suggest the dysregulation of inflammatory cytokines cause and intensify CRF and its related symptoms. 11,12,[57][58][59] In our study, 63% of the patients perceived moderate to vast improvement of improvement in CRF with PG treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies suggest the dysregulation of inflammatory cytokines cause and intensify CRF and its related symptoms. 11,12,[57][58][59] In our study, 63% of the patients perceived moderate to vast improvement of improvement in CRF with PG treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Karacabey (2005) has suggested that the natural defense system of the organism needs to be strengthened to decrease the risk of disease, and to maintain good health, and that the increased body resistance to disease through the strengthening of the immune system could decrease the convalescence time, increase work efficiency, and improve sportive performance. Seruga et al (2008) reported that the systemic effects of pro-inflammatory cytokines are associated with fatigue, depression and cognitive impairment, but physical activity decrease fatigue in patients with cancer by altering cytokine levels. From these studies, it can be inferred that the proper exercise without loading fatigue or stress can contribute to prevention of cancer in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 was also found to drive tumor initiation and subsequent growth and metastasis, with a poor clinical outcome observed in colorectal cancer patients. Through its link with STAT3, it promotes the expression of VEGF and FGF, supporting the rapid vascularization required for tumor growth and metastasis [38,39].…”
Section: Angiogenesis Confirms Metastatic Potential Of Quorum Sensingmentioning
confidence: 99%